2010
DOI: 10.1128/aem.00023-10
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of the c -Type Cytochrome OmcS along Pili of Geobacter sulfurreducens

Abstract: Immunogold localization revealed that OmcS, a cytochrome that is required for Fe(III) oxide reduction by Geobacter sulfurreducens, was localized along the pili. The apparent spacing between OmcS molecules suggests that OmcS facilitates electron transfer from pili to Fe(III) oxides rather than promoting electron conduction along the length of the pili.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
272
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(285 citation statements)
references
References 50 publications
10
272
0
3
Order By: Relevance
“…The pilT-2 gene (GSU0230), encoding one of the four putative pilus retraction ATPases of G. sulfurreducens, was upregulated on both Fe(III) oxide and Mn(IV) oxide (Table 2), and several other putative pilus biogenesis proteins were upregulated on Fe(III) oxide only (Table 3): pilL (GSU2039), pilY1-2 (GSU2038), fimU (GSU2037), pilV-2 (GSU2036) and pilM (GSU2032); or on Mn(IV) oxide only (Table 4): pilP (GSU2029) and pilQ (GSU2028). The upregulation of pilus biogenesis genes is consistent with the proposed route of electron transfer along pili to OmcS to Fe(III) and Mn(IV) oxides (Leang et al, 2010;.…”
Section: Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…The pilT-2 gene (GSU0230), encoding one of the four putative pilus retraction ATPases of G. sulfurreducens, was upregulated on both Fe(III) oxide and Mn(IV) oxide (Table 2), and several other putative pilus biogenesis proteins were upregulated on Fe(III) oxide only (Table 3): pilL (GSU2039), pilY1-2 (GSU2038), fimU (GSU2037), pilV-2 (GSU2036) and pilM (GSU2032); or on Mn(IV) oxide only (Table 4): pilP (GSU2029) and pilQ (GSU2028). The upregulation of pilus biogenesis genes is consistent with the proposed route of electron transfer along pili to OmcS to Fe(III) and Mn(IV) oxides (Leang et al, 2010;.…”
Section: Methodssupporting
confidence: 83%
“…In Fe(III) oxide-grown cells, 28.3 times more omcS and 28.3 times more omcT transcripts were detected compared with Fe(III) citrategrown cells; in Mn(IV) oxide-grown cells, levels of omcS and omcT transcripts were 13.8-fold and 52.2-fold higher, respectively ( Table 1). As noted in the Introduction, previous studies have suggested that OmcS, which is localized along the pili (Leang et al, 2010), is the terminal Fe(III) and Mn(IV) reductase (Mehta et al, 2005;Qian et al, 2011). Despite high levels of expression of omcT, OmcT has been reported to be not abundant in the proteome of Fe(III) oxide-grown cells (Ding et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such biofilms are electrically conductive, inferred by the ability of cells not in direct contact with the anode surface to contribute to current generation (22), and confirmed by two-electrode conductivity measurements (20,23). Geobacter cells possess an abundance of multiheme c-type cytochromes on their outer membrane, in the ECM, and along PilApili (24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Cyclic voltammetry (19,(34)(35)(36)(37) and spectroelectrochemical measurements (38)(39)(40)(41)(42)(43) of actively respiring Geobacter biofilms are consistent with long-range electron transport mediated by sequential electron transfer reactions through a network of bound redox cofactors comprised of ECM c-type cytochromes terminating with electron transfer to the anode surface.…”
mentioning
confidence: 83%
“…S4), which suggests that outer membrane c-cytochromes also contribute to the extracellular reduction of U(VI). It is unlikely that the outer membrane c-cytochrome OmcS, which has been hypothesized to mediate electron transfer between the conductive pili and metals (22), contributed to the pili-mediated reduction of U, because the pRG5::pilA strain expressed OmcS at wild-type levels (Fig. S5) yet reduced more U than the WT P+ (Fig.…”
mentioning
confidence: 99%